Penatalaksanaan Fisioterapi Pada Penderita Asma BronkialeDi Rumah Sakit Khusus Paru Respira Yogyakarta - Setyaningtyas, Laila; , Isnaini Herawati, S.Fis, S.Pd, M.sc (2016)
Background : Bronchial asthma is an inflammatory disorder characterized by airflow obstruction breath and excessive airway response to various forms of stimulation. Airway obstrusction is widespread but variable due to bronchospasm, airway mucosal edema and increase productionof mucus (phlegm) accompanied by blockade (plugging) and airway remodelling. The disease is one form of chonic obstructive the long-term lung disease (COLD) that is characterized by increased airway resistance. Objective : To determine the benefits nebulizer and chest physiotherapy in reducing shortness of breath, increase thoracic expansion, reducing sputum in the airways and increase Peak Expiratory Flow Rate (PEFR) Result : After therapy four times, the results obtained degress T0 : 4 to T4 : 2, margin thorax expansion from the axilla in T0 : 2 cm into T4 : 2,5 cm, of intercostalis IV on T0 : 2,5 cm into T4 : 3 cm, of procesus xypoideus at T0: 3 cm into T6: 3,5 cm. the results of PEFR on T0 : 125 L / min into T6: 250 L / min. results sputum T0 : sputum is located on top of anterior and posterior the right lung lobe and the top of anterior and posterior the left lobe T4: sputum layout is still the same as in T1 but the sound produced ronchi diminishing and virtually disappeared. Conclution : Nebulizer and chest physiotherapy can reducing shortness of breath, increase thoracic expansion, reducing sputum in the airways and increase Peak Expiratory Flow Rate (PEFR)